PENGARUH KECERDASAN EMOSIONAL DAN GAYA HIDUP TERHADAP MANAJEMEN KEUANGAN PRIBADI - Hanna Rosa Tamala Hanna Rosa; Edi Fitriana Afriza; Rendra Gumilar (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The rise of various financial problems among students due to changes in lifestyle that are not balanced with adequate income and without being based on good considerations and in accordance with the order of needs on a priority scale has a serious impact. Poor personal financial management cannot be separated from the influence of emotional intelligence and lifestyle. Personal financial management must be understood and then applied to minimize financial problems and achieve good financial goals. The research aims to determine the influence of emotional intelligence and lifestyle on personal financial management. The population was 110 respondents, Siliwangi University students from the Bogor Region Cluster Class 2020 to 2022 with a NonProbability Sampling sampling technique, namely a saturated sample so the total sample is 110 respondents. The data collection method uses a questionnaire, as well as data analysis techniques using the classic assumption test, multiple linear regression test, coefficient of determination and hypothesis testing. The results of this research show that, partially, there is a significant influence between emotional intelligence on personal financial management, while lifestyle partially has a significant influence on personal financial management. Apart from that, these two variables simultaneously influence personal financial management.